Changes in the immune and endocrine responses of patients with pulmonary tuberculosis undergoing specific treatment - Bongiovanni, Bettina (2012)
We evaluated the immune and endocrine status following antituberculosis (TB) treatment in HIV-negative patients Q1 Q2 with newly diagnosed TB. Treatment led to a decrease in IL-6, IL-1, and C-reactive protein levels. Cortisol levels decreased throughout the anti-TB treatment, particularly after four months, but changes were less pronounced than those seen in proinflammatory mediators. Specific therapy resulted in increased dehydroepiandrosterone (DHEA) levels, which peaked after four months and started to decline after six months of treatment, reaching levels below those detected at inclusion. In most patients, DHEAS levels remained unchanged, although a trend to increased concentrations were observed in a few cases three months after the treatment was finished. Specific therapy also resulted in more balanced cortisol/DHEA and cortisol/DHEAS ratios. Etiologic treatment involves favorable immune and endocrine changes, which may account for its beneficial effects.